(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To identify the factors influencing the health workforce at Chi Linh Medical Center during 2022 - 2024, thereby providing an empirical database for developing strategies to develop, attract, and retain health care human resource. Methods: Combining qualitative research (in-depth interviews, focus group discussions) and quantitative research using secondary data retrospectively collected from personnel records at Chi Linh Medical Center during the period 2022-2024. Results: Facilitators: There were implemented relatively rigorous and transparent recruitment processes, ensuring the quality of new entrants. The leadership demonstrated commitment to providing direction and encouraging professional development, fostering a collaborative and unified working environment. Furthermore, expanded opportunities for short-term training and continuing education significantly enhanced the clinical skills of the staff. Barriers: There were a notable lack of specific incentives and specialized policies for high-level professionals. Compensation, benefits, and overall income remained low relative to the workload. Limited infrastructure and equipment, coupled with high workloads and multi-tasking requirements exerted significant pressure on staff and compromised work efficiency. A segment of the workforce exhibited a tendency to resign or transfer due to perceived limited career advancement and suboptimal working conditions. Conclusion: There were achieved positive transitions in human resource recruitment and the creation of an interactive environment that promotes professional competency. However, health worker incomes failed to meet basic living needs. Work pressure, inadequate facilities, particularly the shortage of high-tech equipment and the inconsistent availability of health insurance-covered medications remained critical challenges that hindered recruitment and the full utilization of human resources.